Управління конкурентоспроможністю туристських дестинацій - Щоголєва, І. В.; Shchogoleva, І. (ЦНТУ, 2017)
В статті розкрито сутність поняття туристських дестинацій, а також параметри оцінки їх конкурентоспроможності. Розглянуто та узагальнено різні аспекти управління конкурентоспроможністю туристських дестинацій, зокрема географічно-територіальний, маркетинговий, продуктовий, ресурсний, економічний та соціальний. Проаналізовано позицію України у світовому рейтингу подорожей та туризму на основі індексу конкурентоспроможності за версією експертів Всесвітнього економічного форуму. Запропоновано шляхи підвищення ефективності управління конкурентоспроможністю туристських дестинацій. In the 21st century, tourism became one of priority development fields of economic and cultural spheres of life of the most countries worldwide. The most diverse places and regions which specialists name destinations become the object of their interest. Keeping, advancement and management of the tourist destination are, surely, the main tasks, when business touches the attractiveness issue of any region. The purpose of the article covers the research of theoretical and practical aspects and determination of ways of its effectivizaton. The tourist destination concept backgrounds, and also the parameters of estimation of its competitiveness, are revealed in the article. Different aspects of the tourist destination competitiveness management, namely: geographically-territorial, marketing, food, resource, economic and social have been considered and generalized. The position of Ukraine in the world rating of trips and tourism on the basis of competitiveness index due to the version of the World economic forum experts has been analyzed. The author offers the ways of effectivizaton of the tourist destination competitiveness management. The ultimate goal of the destination competitiveness increasing and the indicator of management efficiency is socio-economic development of the entire territory, which prognosticates the state of different activity aspects, in particular: normative-legal, organizational, financial, social and communicative.
Tourist destinations competitiveness management
Keywords: туризм; туристська дестинація; конкурентні переваги; конкурентоспроможність; фактори конкурентоспроможності; управління конкурентоспроможністю; tourist destination; competitive advantages; competitiveness; factors of competitiveness; competitiveness management